2016
DOI: 10.1021/acs.bioconjchem.6b00320
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic Carbene–Polyethylenimine Platinum Complexes with Potent in Vitro and in Vivo Antitumor Efficacy

Abstract: The current interest for platinum N-heterocyclic carbene complexes in cancer research stems from their impressive toxicity reported against a range of different human cancer cells. To date, the demonstration of their in vivo efficacy relative to that of established platinum-based drugs has not been specifically addressed. Here, we introduce an innovative approach to increase the NHC-Pt complex potency whereby multiple NHC-Pt(II) complexes are coordinated along a polyethylenimine polymer (PEI) chain. We show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 54 publications
(76 reference statements)
1
32
1
1
Order By: Relevance
“…We recently highlighted that polyethyleneimine (PEI), a polymer widely used as transfection agent, can be used as ligand for N-heterocyclic carbene platinum complexes to generate NHC-Pt-PEI conjugates that induce human cancer cell death in vitro and in vivo [10]. Interestingly, we showed that a part of the cytotoxicity induced by our compounds was independent of nucleus and seemed related to mitochondrial dysfunction.…”
Section: Introductionmentioning
confidence: 90%
“…We recently highlighted that polyethyleneimine (PEI), a polymer widely used as transfection agent, can be used as ligand for N-heterocyclic carbene platinum complexes to generate NHC-Pt-PEI conjugates that induce human cancer cell death in vitro and in vivo [10]. Interestingly, we showed that a part of the cytotoxicity induced by our compounds was independent of nucleus and seemed related to mitochondrial dysfunction.…”
Section: Introductionmentioning
confidence: 90%
“…This is also much higher than known platinum(II) N-heterocyclic carbene complexes thus confirming the positive impact of the anthracene moiety. Indeed, complexes of type (NHC)PtI2(L) have IC50 at a micromolar range typically from 0.5 to 5 µM [47,[50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, little is known about the intracellular cytotoxic mechanism of NHC-Pt complexes mainly due to their novelty [50,51]. We thus decided to conduct several studies on the interaction between DNA and such type of complexes.…”
Section: Introductionmentioning
confidence: 99%
“…50 In fact, measurements of the binding efficiency of the complexes to salmon testes DNA showed increased binding for 5a and 5b (2.03 pmol/µg and 1.03 pmol/µg, respectively) compared to Et3PAuCl (0.11 pmol/µg), but which was still weaker than cisplatin Furthermore, novel mechanistic behaviors were reported for a polymeric formulation of platinum(II) NHC fragments attached to a bidentate polyethylenimine ligand, a known transfection agent (7, Figure 5). 52 Notably, the complex is much more effective than cisplatin and oxaliplatin against HCT-116 (human colorectal adenocarcinoma) cells. Evaluation of the subcellular distribution of 7 demonstrated that only 16% of the total intracellular platinum accumulated in the nucleus while 20% was found in mitochondria.…”
Section: Direct Coordinationmentioning
confidence: 99%